Bargaining power and outside options in the interbank lending market - Puriya Abbassi; Falk Bräuning; Niels Schulze (Financial Management, 2021)
We study the role of bargaining power and outside options with respect to the pricing of over-the-counter interbank loans using a bilateral Nash bargaining model, and we test the model predictions with detailed transaction-level data from the euro-area interbank market. We find that lender banks with greater bargaining power over their borrowers charge higher interest rates, whereas the lack of alternative investment opportunities for lenders lowers bilateral interest rates. Moreover, we find that when lenders that are not eligible to earn interest on excess reserves (IOER) lend funds to borrowers with access to the IOER facility, they do so at rates that are below the IOER rate; in turn, these borrowers put the funds in their reserve accounts to earn the spread. Our findings highlight that this persistent arbitrage crucially depends on lenders' limited bilateral bargaining power. We examine implications of these findings for the transmission of euro-area monetary policy.
Keywords: 650; bargaining power; monetary policy; money market segmentation; over-the-counter market